2008
DOI: 10.1021/bi800723n
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Flippases Translocate Glycerophospholipids and Oligosaccharide Diphosphate Dolichols across the Endoplasmic Reticulum

Abstract: Transbilayer movement, or flip-flop, of lipids across the endoplasmic reticulum (ER) is required for membrane biogenesis, protein glycosylation, and GPI anchoring. Specific ER membrane proteins, flippases, are proposed to facilitate lipid flip-flop, but no ER flippase has been biochemically identified. The glycolipid Glc3Man9GlcNAc2-PP-dolichol is the oligosaccharide donor for protein N-glycosylation reactions in the ER lumen. Synthesis of Glc3Man9GlcNAc2-PP-dolichol is initiated on the cytoplasmic side of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 52 publications
8
129
0
Order By: Relevance
“…Thus, glycerophospholipids, glycosylphosphatidylinositol, dolichol-PP-oligosaccharide, dolichol-P-monosaccharides, dolichyl phosphate, and glucosylceramide must all flip across the ER membrane to support cell growth and metabolism. We recently showed that glycerophospholipids, dolichol-PP-oligosaccharide, and dolichyl-phosphate-mannose are transported across the ER by ATP-independent flippases that can be biochemically resolved (21,51). Because it is likely that dolichyl phosphate is flipped by the dolichol-P-monosaccharide flippases (51) and glycosylphosphatidylinositol is translocated by phospholipid/GlcCer flippases (52), we conclude that the ER has four different lipid flippases.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Thus, glycerophospholipids, glycosylphosphatidylinositol, dolichol-PP-oligosaccharide, dolichol-P-monosaccharides, dolichyl phosphate, and glucosylceramide must all flip across the ER membrane to support cell growth and metabolism. We recently showed that glycerophospholipids, dolichol-PP-oligosaccharide, and dolichyl-phosphate-mannose are transported across the ER by ATP-independent flippases that can be biochemically resolved (21,51). Because it is likely that dolichyl phosphate is flipped by the dolichol-P-monosaccharide flippases (51) and glycosylphosphatidylinositol is translocated by phospholipid/GlcCer flippases (52), we conclude that the ER has four different lipid flippases.…”
Section: Discussionmentioning
confidence: 83%
“…C, purified Yop1-HA was reconstituted into proteoliposomes. Membrane association of Yop1-HA was demonstrated by flotation in a discontinuous sucrose gradient, as described previously (21), using steps of 750, 750, 1000, 1000, and 750 l of 0, 5, 10, 20, and 30% (w/v) sucrose, respectively. The vesicles floated as a sharp band at the interface between the 10 and 20% sucrose layers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon translocation of the heptasaccharide to the luminal site, which is facilitated by Rft1 (11) and another not yet identified protein (12), it is extended by four mannose and three glucose residues deriving from Man-P-Dol and Glc-P-Dol. It has been demonstrated that the pathway operates sequentially in an ordered fashion based on differences in the substrate specificity of the various glycosyltransferases (13).…”
mentioning
confidence: 99%